SINAES no Instituto Federal do Norte de Minas Gerais (IFNMG): políticas, práticas institucionais e a visão de gestores e membros da Comissão Própria de Avaliação (CPA) - Gomes, Daniela Fernandes (2021)
This thesis analyzes the influence of Sinaes on the management actions of the IFNMG. The research has, among its justification factors, the peculiarities and multiplicity performance of the IFs, along with the relevance of Sinaes as an evaluation policy which subsidizes the acts of regulation and supervision of higher education and quality induction. The methodology applied for the case study, with a qualitative approach, used thematic or categorical content analysis based on the different changes in regulatory frameworks related to the evaluation of higher education in the last decade; on the experience of strategic individuals at IFNMG (central administration managers, CPA coordinators and sCPA members), on quality indicators (CE, CPC, IGC, IDD), on evaluation concepts (CC and CI); in the internal and external evaluation reports and institutional documents of the IFNMG. The main theoretical foundations that supported the research took into account the context of neoliberal policies and ideology and their effects on higher education, especially with regard to its expansion and reconfiguration; the higher education assessment policy; the constitution of IFs as IES and Sinaes as a mechanism for their evaluation and regulation. It was found that Sinaes has a considerable influence on the planning of the IFNMG expressed in its Institutional Development Planning-IDP and that the institution lacks internal evaluative policies that take into account its dimension of proceeding. There is no systematic planning in the institution in order to make use of the results of Sinaes procedures to promote improvements in management actions, nor there is an organization to articulate the data obtained with this goal. However, it was verified the existence of a positive evolution of most of its evaluation results, especially of the internal evaluations and external evaluations in loco of courses, in addition to a developing evaluation culture. It is concluded that, although the institution does not have higher education as its main objective, it is surrounded by different procedures that assess it in a partial and, to a certain extent, fragmented way. In this sense, it is necessary to think out actions and management tools that organize and associate the assessment specified in Sinaes, and regulatory demands, to the institutional planning, creating strategies that involve the participation of the academic community in the process.